2007
DOI: 10.1093/ecam/nem099
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Caspase‐3 and Bcl‐2 Expression in Dalton′s Lymphoma Ascites Cells by Abrin

Abstract: The role of abrin, a toxic lectin isolated from seeds of Abrus precatorius Linn in inducing apoptosis in murine Dalton's Lymphoma Ascites (DLA) cells was evaluated. Abrin when incubated at the concentration of 10 ng per million DLA cells could bring about cell death as typical morphological changes with apoptosis. However, necrotic cell death dominated when a higher dose of abrin was used. DNA samples, isolated from DLA cells treated with abrin showed fragmentation. Abrin brought about induction of apoptosis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Caspase-8 is activated after receiving stimulus signals and subsequently triggers the caspase protease that activates the downstream chain of hydrolases and then further activates the effector caspase-3. Studies have demonstrated that abrin P2 induces apoptosis via the mitochondrial pathway, specifically via Cyt c release or regulation of caspase-3 and Bcl-2 expressions in different types of cancer cells [16][17][18]. In this study, Z-VAD-FMK, a broad-spectrum caspase inhibitor, was found to partially abrogate abrin P2-induced apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…Caspase-8 is activated after receiving stimulus signals and subsequently triggers the caspase protease that activates the downstream chain of hydrolases and then further activates the effector caspase-3. Studies have demonstrated that abrin P2 induces apoptosis via the mitochondrial pathway, specifically via Cyt c release or regulation of caspase-3 and Bcl-2 expressions in different types of cancer cells [16][17][18]. In this study, Z-VAD-FMK, a broad-spectrum caspase inhibitor, was found to partially abrogate abrin P2-induced apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…Interestingly, overexpression of bcl-2 in DAOY and U87 cells was associated with a decrease in production of caspase 3. Although the mechanism for this coordinate, complementary regulation of expression is not known, it has recently been reported in Dalton's lymphoma ascites cells treated with the chemotherapeutic natural product, abrin [19]. Nonetheless, in bcl-2-transfected DAOY and U87 cells, increased [(relative Bcl-2 content)(relative caspase-3 content)] is associated with increased sensitivity to NCS (Fig.…”
Section: Effect Of Transfection With a Bcl-2 Expression Construct On mentioning
confidence: 93%
“…Abrin isolated from seeds of Abrus precatorius [53], extract of Phyllanthus amarus [54] and Drosera indica [55] activation of caspase activated DNase mediated nuclear fragmentation has been studied in Dalton's lymphoma [56].…”
Section: T-cells Obtained Frommentioning
confidence: 99%